Web-Based Time-Sheet System - Abu-Shaheen, Majd; , Umi Fadlillah, ST. MEng (2016)
Web-based time-sheet system is a web application that provides an automated method of tracking work time for employees by enabling the manger to track their work time, this system helps in assigning projects to specific employees, also it measures the performance and productivity, as well as providing an automated method of calculating salary for employees based on their total work time. The system, in addition, provides a direct communication among the employees and the manger. One important advantage of the system is that each employee can log into his account to do the assigned projects. An employee, a manager and an admin have different prerogatives according to their roles. Besides, the system has been built in asp.net, C#, Ajax and JavaScript, and using SQL server database. Web-based timesheet system has been successfully tested at Rami Awad Establishment with high level of satisfaction as the questionnaire results showed.